The Relationship Of Information Sources With Pregnant Women's Interest In Participating The Covid-19 Vaccination Program - Basselo, Asri (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2023)
Vaccination causes controversy for some people, because there are doubts about vaccine development, because the vaccine development time is quite short, around one year. The aim of this research is to analyze the relationship between information sources and pregnant women's interest in participating in the Covid-19 vaccination program at the Sowi Community Health Center. This type of research is analytical research with a cross-sectional study approach where the independent variable and dependent variable are measured at the same time. The sample in this study was all pregnant women in the second and third trimesters who visited the Sowi Community Health Center using a total sampling technique. This research uses human research subjects, namely 77 respondents who will be given a questionnaire. The data taken is primary data and data analysis uses the Chi-Square test. The research results show that there is no relationship between the source of information and the interest of pregnant women in participating in the Covid-19 vaccination program at the Sowi Community Health Center with a p value > α value (0.05). The conclusion is that the source of information is not a factor that can influence pregnant women's interest in participating in the Covid-19 vaccination program.